Explanation:
16.................................................
Given
- Equation ax² + bx + c = 0
- One of the roots is twice the other
To find
Solution
Let the roots be p and q
The sum and product of the roots:
The sum of the roots, considering p = 2q,
And
The product of the roots, considering p = 2q:
And
Substitute q with -b/(3a)
- 2(-b/(3a))² = c/a
- 2b²/(9a²) = c/a
- 2b² = 9a²(c/a)
- 2b² = 9ac
=================================================
17. .................................................
Given
Quadratic equation
- ax² = bx + c = 0, with equal roots
To find
Solution
Equal roots means the discriminant is zero:
- D = √b² - 4ac
- √b² - 4ac = 0
- b² - 4ac = 0
- b² = 4ac